A Critical Legal and Practical Appraisal of Ethiopian Fault Based Liability Rules - Silesh, Gizachew; Andargie, Haile; Amare, Esubalew; Hailu, Honelign; Addis, Abay (Bahir Dar University Journal of Law, 2023)
Ethiopia’s Civil Code governing tortious liability was adopted six decades ago and is still applicable without any amendment. The basic purpose of this research is to explore the shortfalls and practical application of the Ethiopian tort law on liability arising from fault. To this effect, a qualitative research method is employed. Therefore, relevant laws are critically analyzed and data is collected by interviewing judges, attorneys, and law professors. The research findings reveal that the special part of the fault-based liability section of the Code is insufficient and does not adequately address breaches of human rights recognized under the FDRE constitution. The findings of the research also demonstrate that some of the provisions on fault-based liability are not practically applied by courts. Therefore, this article suggests an amendment to accommodate constitutional stipulations. The article also recommends extending the list of special faults to embrace emerging issues.